2006
DOI: 10.2527/jas.2005-611
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on pregnancy rate in beef cattle1

Abstract: Ten years of calving records were examined from Bos taurus crossbred cows (mean of 182 cows/ yr) to quantify the effects of environmental conditions during the breeding season on pregnancy rate. Estimated breeding dates were determined by subtracting 283 d from the calving date. Relationships were determined between the proportion of cows bred during the periods from the beginning of the breeding season until d 21, 42, and 60 of the breeding season and the corresponding environmental variables. Weather data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
81
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 8 publications
3
81
0
1
Order By: Relevance
“…Morrison (1983) reported that RH affects the rate of evaporation from surfaces, so it would be expected to also affect evaporative heat loss. Likewise, SR has been found to influence body temperature and DWI Amundson et al, 2006;Mader et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Morrison (1983) reported that RH affects the rate of evaporation from surfaces, so it would be expected to also affect evaporative heat loss. Likewise, SR has been found to influence body temperature and DWI Amundson et al, 2006;Mader et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In general, a THI of 70 or 72 would be considered a decreased threshold, although differences among animals do exist with high producing animals with increased metabolic heat load having decreased heat stress thresholds (Mader, 2003). Inflection points would possibly represent a threshold or shift in some physiological or biological response due to changing environmental conditions (Amundson et al, 2006). In addition, Mader (2003) and Amundson et al (2006) established the importance of Tmin in energy balance of cattle, mainly used as a strategy to dissipate heat during the night.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In females, heat stress compromises oocyte growth by altering progesterone, luteinizing hormone and follicle-stimulating hormone secretion and dynamics during the estrous cycle (Ronchi et al, 2001). Moreover, heat stress may reduce summer fertility in dairy and beef cows by causing poor estrous expression due to reduced estradiol secretion from the dominant follicle developed in a low luteinizing hormone environment (Biggers et al, 1987; De Rensis and Scaramuzzi, 2003;Amundson et al, 2006). About a 20% to 27% drop in conception rates (Lucy, 2002; Chebel et al, 2004) or decrease in 90-day non-return rate to the first service in lactating dairy cows (Al-Katanani et al, 1999;Ravagnolo and Misztal, 2002) occurs in summer.…”
mentioning
confidence: 99%